1990
DOI: 10.1152/ajpendo.1990.258.6.e1014
|View full text |Cite
|
Sign up to set email alerts
|

Placental growth hormone as a potential regulator of maternal IGF-I during human pregnancy

Abstract: Ninety-three healthy women were investigated during normal pregnancy, and 177 blood samples were obtained at various gestational stages. In 8 of the women, serial measurements were obtained over a period of 16-34 wk from 8 to 40 wk of gestation. In 13 women, daily blood samples were obtained from day 0 to day 6 after delivery. Insulin-like growth factor I (IGF-I) and human placental lactogen (hPL) were measured by radioimmunoassays. Growth hormone (GH) was estimated by two monoclonal antibody-based radioimmuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
83
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 15 publications
9
83
1
1
Order By: Relevance
“…We did not confirm recently reported data that PGH levels were different according to the sex of the fetus (41). PGH was the major determinant of IGF-I concentrations, confirming the strong correlation between both variables in normal and IUGR pregnancies (3,4,10). We have reported that PGH and IGF-I concentrations were within the normal range and were highly correlated in a pregnant woman with absent GH secretion owing to pit-1-deficiency (35).…”
Section: Discussionsupporting
confidence: 68%
“…We did not confirm recently reported data that PGH levels were different according to the sex of the fetus (41). PGH was the major determinant of IGF-I concentrations, confirming the strong correlation between both variables in normal and IUGR pregnancies (3,4,10). We have reported that PGH and IGF-I concentrations were within the normal range and were highly correlated in a pregnant woman with absent GH secretion owing to pit-1-deficiency (35).…”
Section: Discussionsupporting
confidence: 68%
“…In the patient with a TSH-secreting macroadenoma given octreotide during the third trimester of gestation, serum hPGH and IGF-I levels were higher in late pregnancy than in first and second trimesters of gestation and decreased rapidly after elective cesarean section. Therefore, changes in hPGH and IGF-I levels were comparable to those reported during normal pregnancy (2,3). The normal neonate at birth suggests physiological IGF-I secretion during pregnancy and implies that IGF-I levels were biologically sufficient for normal fetal development.…”
Section: Discussionsupporting
confidence: 70%
“…It appears likely that hPGH is biologically active as a growth-promoting hormone; in the second half of pregnancy, serum insulin-like growth factor I (IGF-I) increases when hPGH concentrations are high, whereas pituitary GH secretion is suppressed (2,3). In nonpregnant women, pituitary GH secretion is pulsatile as a result of the actions of neurotransmitters and neuropeptides, with both stimulatory (GHRH) and inhibitory (somatostatin) effects.…”
mentioning
confidence: 99%
“…It is found in high concentrations during the last half of pregnancy, and at the same time pituitary GH is virtually absent in plasma (4,5). The regulation and physiology of PGH is far from being understood, but the secretion of PGH is described as non-pulsatile (7).…”
Section: Discussionmentioning
confidence: 99%
“…Secretion is evident early in the first trimester (3), and PGH gradually replaces pituitary growth hormone (GH), which is stabilised at very low, but still detectable levels, in the last half of pregnancy (2,4,5). Maximum levels of PGH approach acromegalic levels of GH around gestational weeks 35 -37 (3 -6).…”
Section: Introductionmentioning
confidence: 99%